Tanzimat Dönemi’nden Cumhurbaşkanlığı Hükümet Sistemine kadar Türk idari teşkilatında istişari kurullar - Kocabaş, Sadık; Kocabaş, Sadık (Batı Karadeniz Akademisyenler Derneği (BAKAD), 2023)
Tanzimat Dönemi gerek Osmanlı Devleti’ni gerekse Türkiye Cumhuriyeti’ni farklı boyutlarda etkilemiştir. Hiç şüphesiz ki devletin idari teşkilatlanması da etkilenen boyutların başında gelir. Buna göre Tanzimat Dönemi ile birlikte kurumsallaşan idari yapılardan bazıları günümüze kadar gelmiştir. Bu idari yapılardan biri de istişari kurullardır. İşte bu çalışmanın konusu; 2. Mahmud ile başlayan, Tanzimat Fermanı’nın ilanı ile artarak devam eden ve 1. Meşrutiyet’e kadar uzanan reform döneminde, idari teşkilatımızda ortaya çıkan istişari organlar ve bunların Cumhurbaşkanlığı hükümet sistemine geçmeden önceki döneme kadar yani parlamenter sistemin son döneminde görülen yansımaları olacaktır. Buna göre çalışmada öncelikle Osmanlı Devleti’nde meşveret usulüne değinilecek, daha sonra evvela merkezde oluşan, sonra da taşrada oluşan istişari kurullar, parlamenter sistemin uygulandığı son yıllardaki karşılıkları ile verilecektir.

The Tanzimat Period affected both the Ottoman Empire and the Republic of Türkiye in different dimensions. Undoubtedly, the administrative organization of the state is one of the most affected dimensions. Accordingly, some of the administrative structures institutionalized with the Tanzimat Period have survived to the present day. One of these administrative structures is advisory boards. Therefore, here is the subject of this study; during the reform period, which started with Mahmud II and continued with the declaration of the Hatt-ı Sherif of Gülhâne and extended until the First Constitutional Period, there will be advisory divisions that emerged in our administrative organization and their reflections in the last period of the parliamentary system. Accordingly, in the study, firstly, the consultation method in the Ottoman Empire will be mentioned, then the advisory boards formed first in the center and then in the provinces will be given with their equivalents in the last years when the parliamentary system was implemented.
Consultative committees in the Turkish administrative organization from the Tanzimat reform era to the presidential government system
Keywords: Tanzimat dönemi; Cumhuriyet dönemi; Tanzimat reform era; Republican era